PO 119 - Anestesia de Urgência em Síndrome de Stiff Person – um desafio anestésico - Pinto, A. Sofia; Sousa, Bárbara; Portugalyan, Mihran; Delgado, André; Godinho, Pedro; Carmona, Cristina (Journal of the Portuguese Society of Anesthesiology, 2023)
x